2012
DOI: 10.1098/rspb.2011.2464
|View full text |Cite
|
Sign up to set email alerts
|

Modelling seasonal variations in the age and incidence of Kawasaki disease to explore possible infectious aetiologies

Abstract: The average age of infection is expected to vary during seasonal epidemics in a way that is predictable from the epidemiological features, such as the duration of infectiousness and the nature of population mixing. However, it is not known whether such changes can be detected and verified using routinely collected data. We examined the correlation between the weekly number and average age of cases using data on pre-vaccination measles and rotavirus. We show that age -incidence patterns can be observed and pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 34 publications
1
24
0
Order By: Relevance
“…Another way to summarize the changing age-profile of infection during the course of an epidemic is by the correlation between mean age in a given week and incidence in that week, which we refer to as the age-incidence pattern [30]. By examining the correlation coefficient between the weekly incidence of observed cases and the average age of such cases at different lags, it was shown that determining whether this correlation is highest at negative versus positive lags (i.e.…”
Section: Trends Relative To the Stage Of The Epidemic Curvementioning
confidence: 99%
See 2 more Smart Citations
“…Another way to summarize the changing age-profile of infection during the course of an epidemic is by the correlation between mean age in a given week and incidence in that week, which we refer to as the age-incidence pattern [30]. By examining the correlation coefficient between the weekly incidence of observed cases and the average age of such cases at different lags, it was shown that determining whether this correlation is highest at negative versus positive lags (i.e.…”
Section: Trends Relative To the Stage Of The Epidemic Curvementioning
confidence: 99%
“…By examining the correlation coefficient between the weekly incidence of observed cases and the average age of such cases at different lags, it was shown that determining whether this correlation is highest at negative versus positive lags (i.e. whether the average age is greatest before or after the epidemic peak) helps to identify which age groups are more likely to be infected early on in the epidemic [30]. …”
Section: Trends Relative To the Stage Of The Epidemic Curvementioning
confidence: 99%
See 1 more Smart Citation
“…Thus, prevailing theories regarding infectious etiology assume that KD results from an abnormal immune response to a first infection in predisposed individuals (32). The rarity of the disease over the first few months of life suggests that maternal passive immunity plays a protective role against the inciting The relationship between Kawasaki disease (Kd) incidence for children <5 y (boxes) or <18 y (diamonds) and adult soy consumption per day for three major ethnic groups in hawaii (Caucasian in white, native hawaiian in gray, and Japanese in black).…”
Section: Tyrosine Protein Kinase Inhibition and Isoflavonesmentioning
confidence: 99%
“…Epidemiologic tools have traditionally been used to determine the etiology of infectious diseases, but, 50 years later, the application of these approaches to the study of KD has only yielded limited insights. [12] Although KD is the most common cause of acquired heart disease in children in countries where rheumatic heart disease has waned, the etiology remains a mystery. [3] The current paradigm is that KD is an immunologic reaction to an environmental trigger in genetically susceptible children.…”
mentioning
confidence: 99%